2019
DOI: 10.1177/2167696819876752
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Family Financial Socialization and Emerging Adults’ Financial Well-Being: A Multi-Informant Approach

Abstract: This study’s purpose is to investigate how implicit family financial socialization (family communication quality and family economic enmeshment) influences emerging adults’ objective and subjective financial well-being mediated by the degree to which the emerging adult child adopts their parents as financial role model. Using a multi-informant approach, structural equation model family-level analyses were conducted based on responses from mothers, fathers, and emerging adults in 160 Italian families. Results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 23 publications
4
78
0
4
Order By: Relevance
“…Consequently, we suggest that the General Subjective Financial Well-being factor can also be used alone as a measure of subjective financial well-being (when the research is just focused on the core of the construct). For example, we used only this factor as the outcome of the family financial socialization process (Lanz, Sorgente, & Danes, accepted).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we suggest that the General Subjective Financial Well-being factor can also be used alone as a measure of subjective financial well-being (when the research is just focused on the core of the construct). For example, we used only this factor as the outcome of the family financial socialization process (Lanz, Sorgente, & Danes, accepted).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, research has shown that parental financial socialization affects their financial behaviour (Jorgensen & Savla, 2010; Kim & Chatterjee, 2013; Otto, 2013; Shim et al, 2009; Sohn, Joo, Grable, Lee, & andMinjeung Kim., 2012). The effect of financial socialization in influencing well‐being has received more attention recently (Sorgente & Lanz, 2017; Lanz et al, 2019; for review see Gudmunson & Danes, 2011). Sansone et al (2018) evaluated the relationship between receiving an allowance (pocket money) in childhood and financial confidence in adulthood.…”
Section: Conceptual Modelmentioning
confidence: 99%
“…In this study, the focus was on parental socialization because parents are a key socialization agent (Drever et al, 2015; Lanz et al, 2019). Financial socialization was considered to include discussion with parents during childhood on savings, investing, financial products, budgeting and spending behaviour.…”
Section: Conceptual Modelmentioning
confidence: 99%
See 2 more Smart Citations